Pengalaman Ibu Menghadapi Remaja Pubertas Usia 12-15 Tahun - Hesty Hesty (Prosiding Seminar Kesehatan Nasional, 2022)
Adolescence is a period of transition from children to adults. The transition that occurs psychological factors and physical factors. Changes in body, interests and roles expected by social groups raise new problems. Changes in values as a consequence of changes in interests and behavior patterns. Being ambivalent about change, adolescents want and demand freedom, but are afraid of taking risks and doubting their ability to overcome them. This research is a qualitative research with a phenomenological approach. The data collection method used was an in-depth interview/observation method in the form of observation with a question sheet interview guide, tape recorder, and stationery. Time of implementation of three meetings on 5 participants. The population is all mothers who are married for 20 years and are under 30 years old. Sampling in this study is to use the snowball sampling method. This study produced 3 themes, 1. Mother's efforts to understand adolescent puberty. Categories of being a friend, being an educator, being a protector/supervisor. 2. Efforts made by mothers when teenagers experience inner turmoil. Categories of being a listener, being trustworthy, being involved in youth problems, looking for the causes of problems. 3. Mother's efforts to monitor adolescent behavior. Category ask for permission, be on time, keep yourself in the association. Mothers make efforts to understand puberty teenagers such as being good friends, being parents who educate their children in a better direction and being active parents. When teenagers experience inner turmoil, it is to be a child's friend, to be a good listener, to be patient and not emotional, not to judge, to make children believe in protection, to motivate children that they have good potential.